2022
DOI: 10.1002/mawe.202100115
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of structural steel to liquid metal embrittlement during hot‐dip galvanizing in zinc 5 %‐aluminum alloy

Abstract: The phenomenon of liquid metal embrittlement has been known in the field of batch hot-dip galvanizing for decades. With the increasing use of zinc alloys with higher content of aluminum, the question arises regarding the specific liquid metal embrittlement effects of such alloys on structural steels. The influence of a zinc 5 %-aluminum alloy during galvanizing on structural steel grades S355 and S700 was investigated and compared with the results obtained in a conventional pure zinc melt. Furthermore, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The latter leads to the transformation of the pure zinc phase into Zn-Fe phases process provides a higher preheating temperature and lower zinc bath temperature owing to a significantly lower thermal stress in the galvanized steel, making it more advantageous for temperature control [22]. On the other hand, tests showed that the impact of the liquid melt on the steel's grain structure and thus its embrittlement potential is lower with the HDG Zn5Al method [23]. Following this, investigations were focused on sections galvanized in the HDG Zn process.…”
Section: Macroscopic and Microscopic Examination Of Zinc Coatingsmentioning
confidence: 99%
“…The latter leads to the transformation of the pure zinc phase into Zn-Fe phases process provides a higher preheating temperature and lower zinc bath temperature owing to a significantly lower thermal stress in the galvanized steel, making it more advantageous for temperature control [22]. On the other hand, tests showed that the impact of the liquid melt on the steel's grain structure and thus its embrittlement potential is lower with the HDG Zn5Al method [23]. Following this, investigations were focused on sections galvanized in the HDG Zn process.…”
Section: Macroscopic and Microscopic Examination Of Zinc Coatingsmentioning
confidence: 99%